Biodegradation of sodium lauryl ether sulfate (SLES) contamination by Pseudomonas aeruginosa isolates - AL-Zamili, Hussein Ali Awadh; Al-Mayaly, Ithar Kamil (Brawijaya University, 2024)
Sodium lauryl ether sulfate (SLES) is a surfactant commonly used in the formulation of detergents, which is typically disposed of in wastewater treatment plants. The current study describes the effectiveness of bacteria isolated from Iraqi wastewater to remove SLES. 16S rRNA genetic analysis revealed that this strain is Pseudomonas aeruginosa. Three temperatures (30, 35, and 40oC) and pH values (5,7, and 9) were chosen for this study, and three concentrations of SLES (25, 50, and 100 mg/L) were used. The SLES anionic surfactant showed that the best biodegradation by Pseudomonas aeruginosa was at a temperature of 30oC and both pH 7 and 9, while the removal percentages for them were 98.44% and 96.36%, respectively, at 25 mg/L of SLES. The outcomes of this study revealed the potential and significance of SLES removal in actual effluents by aerobic biodegradation. The ability of this bacterium to degrade SLES makes the bacterium an important tool for bioremediation.